KANDUNGAN HARA FOSFOR DAN KALIUM DI SEKITAR PERAKARAN TANAMAN UBI KAYU (Manihot Esculenta Cranz) - Noviane Stela Tampil; Djoni Kaunang; Tilda Titah (COCOS, 2022)
ABSTRACTCassava is a food crop that is widely grown in the village of Salurang, Tabukan Selatan TengahDistrict. To develop this plant so that it produces better, it is necessary to conduct research onthe availability of nutrients around the roots. P and K elements are elements needed by cassavaplants, therefore it is necessary to research the availability of nutrients around the roots. Thisstudy aims to determine the nutrient content of phosphorus and soil potassium around the rootsof cassava. The benefit of this research is to determine the right fertilizer in to increase theproduction of cassava plants. The research method used a survey method with purposivesampling on cassava plants which have tubers and have not. Sample analysis using the dry soiltest (PUTK) version 1.0. Bogor Soil Research Institute The results of the analysis showed thatthe phosphorus nutrient content around the roots of the tuberous cassava plants ranged from lowto moderate, while potassium was low to high. Cassava plants that have not been rooted showthat the phosphorus content is moderate, while potassium ranges from moderate to high.Keywords: Phosphorus and Potassium Nutrients